Significance of minor ST segment and T wave changes in the resting electrocardiogram of asymptomatic subjects. Issue 1 (January 1981) - Joy, M; Trump, D W
Abstract : Sixteen thousand resting electrocardiograms were performed on 14000 United Kingdom professional aircrew and air traffic control officers over a two-year period; 103 asymptomatic men with minor ST segment and T wave changes at rest were assessed by exercise electrocardiography and 19 responded abnormally. Five subjects had proven coronary artery disease, one hypertrophic obstructive cardiomyopathy, and one left ventricular dilatation on echocardiography. Eleven subjects were not investigated, of whom three had strongly positive exercise responses. One subject had a false positive response and assuming a false negative response of less than 2 per cent, then a sensitivity of 80.0 per cent, a specificity of 89.1 per cent, a predictive value for the exercise electrocardiogram of 44.46 per cent and for the resting electrocardiogram of 7.8 per cent is obtained. T wave changes induced by hyperventilation were common (53.4% of all). Ten (18.2%) subjects with hyperventilation-induced T wave changes responded abnormally to exercise, three having angiographically proven coronary artery disease lending little support to the contention that the two entities rarely coexist. In spite of the low return from routine electrocardiograms in a population with a low prevalence of coronary artery disease, three-eighths of those with significant coronary artery disease presented with minor ST segment and T wave changes on their resting electrocardiograms.